ANALISIS BIAYA MEDIS LANGSUNG PASIEN RAWAT INAP BEDAH UROLOGI DI RSUD KOTA YOGYAKARTA - Supadmi, Woro; Feangi, Yanti Fitriani; Basuki, Adriyanto Rochmad; Kristina, Susi Ari Kristina; Supadmi, Woro Supadmi; Kristina, Susi Ari (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Urological surgical procedures, such as urolithiasis and benign prostatic hyperplasia (BPH), continue to increase with high recurrence rates. Limited treatment facilities and the risk of antibiotic resistance can affect the cost burden. This study aims to determine the alignment of direct medical costs with INA-CBG’s claim rates and to identify variables influencing total direct medical costs. The study employs an observational approach with a retrospective design. Samples were selected using purposive sampling with inclusion criteria. Data were collected from electronic medical records and financial reports. Direct medical costs were calculated based on all cost components using a hospital perspective approach. Data analysis used univariate, bivariate, and multivariate tests. The average total direct medical costs for urology patients were Rp 9,962,325 ± Rp 1,699,707.79, while the INA-CBG’s claim rates were Rp 9,600,328 ± Rp 1,853,291.26. There were differences in direct medical costs based on age (p-value 0.024), care class (p-value 0.035), and length of stay (LOS) (p-value 0.000). Regression analysis shows that LOS and care class have a statistically significant impact on total direct medical costs (p-value < 0.05). There is a difference between the actual costs borne by the hospital and the INA-CBG’s claim rates.